1991
DOI: 10.1177/155005949102200109
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Extension of P50 Findings in Schizophrenia

Abstract: In a paired click "conditioning (S1), Testing (S2)" paradigm the amplitudes of responses to (S1) as well as the degree of attenuation of S2 as compared to S1 (S2/S1) were studied in two schizophrenic groups. Thirteen undifferentiated/disorganized (US) and thirteen paranoid (PS) patients were compared to thirteen age and sex matched normal volunteers. The US patients had significantly lower (S1) response amplitudes (P less than 0.001), as well as degree of attenuation of the response to (S2) (P less than 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(97 citation statements)
references
References 7 publications
7
88
0
1
Order By: Relevance
“…Our hypothesis was based on evidence implicating glutamatergic and cholinergic receptors in sensory gating (Adler et al, 1986;Luntz-Leybman et al, 1992;Miller et al, 1992a;Bickford and Wear, 1995) and on data showing that cortical and CSF KYNA levels are elevated in schizophrenia (Erhardt et al, 2001;Schwarcz et al, 2001), a disorder characterized by marked auditory gating deficits (Adler et al, 1982;Boutros et al, 1991;Jin et al, 1997;Clementz et al, 1998a, b;Patterson et al, 2000). Since KYNA penetrates the bloodbrain barrier very poorly (Fukui et al, 1991), an indirect approach was implemented, involving blockade of the PBCD-sensitive transporter alone and in conjunction with the administration of KYNA's immediate bioprecursor KYN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis was based on evidence implicating glutamatergic and cholinergic receptors in sensory gating (Adler et al, 1986;Luntz-Leybman et al, 1992;Miller et al, 1992a;Bickford and Wear, 1995) and on data showing that cortical and CSF KYNA levels are elevated in schizophrenia (Erhardt et al, 2001;Schwarcz et al, 2001), a disorder characterized by marked auditory gating deficits (Adler et al, 1982;Boutros et al, 1991;Jin et al, 1997;Clementz et al, 1998a, b;Patterson et al, 2000). Since KYNA penetrates the bloodbrain barrier very poorly (Fukui et al, 1991), an indirect approach was implemented, involving blockade of the PBCD-sensitive transporter alone and in conjunction with the administration of KYNA's immediate bioprecursor KYN.…”
Section: Discussionmentioning
confidence: 99%
“…The diminished response to the second tone is thought to reflect the neural processes involved in gating sensory input and is typically quantified as the ratio of test to conditioning (T/C) response amplitude (Adler et al, 1999;Light and Braff, 1999). Numerous studies have demonstrated that persons with schizophrenia exhibit a blunted response to conditioning stimuli and a failure to show the characteristic reduction in ERP amplitude to the test stimulus (Adler et al, 1982;Boutros et al, 1991;Jin et al, 1997;Clementz et al, 1998a, b;Patterson et al, 2000). Notably, these deficits are strongly correlated with neuropsychological measures of attention (Erwin et al, 1998) and vigilance (Cullum et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, schizophrenia patients and their first-degree relatives exhibit a smaller reduction in the startle response or, in other words, show reduced PPI (Cadenhead et al, 2000;Geyer and Braff, 1987;Swerdlow et al, 1994;Swerdlow and Geyer, 1998). In addition, investigators have also developed protocols to assess auditory gating directly in the brain by using surface electrodes or, in animals, intracranial electrodes, and have found similar results (Adler et al, 1982;Boutros et al, 1991;Clementz et al, 1997;Connolly et al, 2003;Erwin et al, 1991;Freedman et al, 1996;Judd et al, 1992;Stevens et al, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…The P50 is measured via electroencephalography (EEG), where it is maximal at the vertex, and suppression is described as a ratio (ie Click 2 PS0 amplitude/Click 1 P50 amplitude) or difference score (ie Click 2 P50 amplitudeÀClick 1 P50 amplitude). Normal control participants normally exhibit suppression in the range of 50-70% , while it has been demonstrated that patients with schizophrenia display significantly lower P50 suppression (Adler et al, 1982;Boutros et al, 1991;Light et al, 2000;Ward et al, 1996;Yee and White, 2001;Braff et al, 2007), which is interpreted as reflecting a deficit in 'sensory gating' (Adler et al, 1982). Analogous to the PPI findings, there is also some evidence that P50 suppression deficits in schizophrenia may be normalized with the use of atypical antipsychotic drugs (Light et al, 2000;Nagamoto et al, 1996Nagamoto et al, , 1999Adler et al, 2004;Becker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%